Social media as a marketing tool: the effectiveness of facebook towards online brand awareness (FAME cosmetics). A study on Kota Kinabalu facebook users perspective / Siti Nur Anisah Rosli - Rosli, Siti Nur Anisah (2016)
FAME Cosmetics is a growing Malaysian local cosmetics company which has been introduced into the market since 2016. They started their business by producing the most famous liquid lipstick with various choices of colours that has been popularly chased by the trendy people nowadays. This is the right time for this company to actually spread the awareness of their brand. They only have to choose the right strategy to make the people aware of their brand and their products. Facebook is one of the widely used social media that might have the power to spread awareness of a brand. Thus, this research is to identify the best strategy in Facebook that the FAME Cosmetics can focus more to create its brand awareness. The respondents are selected randomly from the Kota Kinabalu Facebook users. The total of 201 questionnaires was distributed online to the respondents.